Competitiveness as a Decisive Criterion for Sustainability - Matolcsy, György (Public Finance Quarterly, 2020)
Competitiveness and sustainability are inseparable concepts. Competitiveness cannot be interpreted in the short term, and thus it cannot exist without sustainability as well. At both the corporate and national economy level, only those who can maintain their outstanding performance, in the long run, are the winners in global competition. There are two roads to achieving these two goals simultaneously, and they can even be followed at the same time. On the one hand, moving away from quantitative factors towards quality, and on the other hand, looking for new resources and making old resources unlimited by using them in a sustainable, “green” manner. With the development of digitalisation, data is becoming a more important resource than ever before, while money and access to energy may become unlimited. No segment of the economy can ignore revolutionary changes, such as the green and digital transition, but proper cooperation between the state and the market is necessary to achieve and maintain competitiveness and sustainability.